2016
DOI: 10.1121/1.4967157
|View full text |Cite
|
Sign up to set email alerts
|

Perception of music dynamics in concert hall acoustics

Abstract: Dynamics is one of the principal means of expressivity in Western classical music. Still, preceding research on room acoustics has mostly neglected the contribution of music dynamics to the acoustic perception. This study investigates how the different concert hall acoustics influence the perception of varying music dynamics. An anechoic orchestra signal, containing a step in music dynamics, was rendered in the measured acoustics of six concert halls at three seats in each. Spatial sound was reproduced through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Pätynen and Lokki [6] is a second paper based on the same study as Lokki [1]. They confirmed the hypothesis that concert halls render the performed music dynamics differently, and with various perceptual aspects.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Pätynen and Lokki [6] is a second paper based on the same study as Lokki [1]. They confirmed the hypothesis that concert halls render the performed music dynamics differently, and with various perceptual aspects.…”
supporting
confidence: 53%
“…Perhaps the most interesting recent hall typology investigation paper is Pätynen and Lokki [7]. Rather than listening tests, this study used the same six halls as references [1,6], but measured a physiological response related to emotional arousal, namely skin conductance, as well as recording listening preferences. They found that rectangular-shaped concert halls evoked higher subjective impact and emotional response than the other types of included concert halls, including the Berlin Philharmonie and Helsinki Musiikkitalo surround form halls.…”
mentioning
confidence: 99%
“…Recently, the research group at Aalto University has taken up the topic of dynamics anew, demonstrating that dynamic spatial responsiveness is related to changes in instrument frequency responses and directivity at higher dynamic levels [11][12][13][14]: due to greater binaural sensitivity to high frequencies at lateral angles, an increased spatial impression results from the additional higher harmonics that are generated when instruments are played loudly. However, little-known research published by Wettschurek [15] in 1978 demonstrates that the connection between dynamics, loudness, and spatial impression is linked to other fundamental processes in the human hearing system, in particular how reflections from different directions are masked or unmasked at different overall listening (dynamic) levels.…”
Section: (Dynamic) Spatial Responsivenessmentioning
confidence: 99%
“…As mentioned before, the positioning of the terms may not represent factual truth about the associations between the terms per se, butit is based on our recent research [21,19,20,27]. Our objective has been to present the terms as logically as possible based on the literature and the authors' current understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Theyare volume [4], level, strength and body [32]. In addition, acknowledging the fact that the sensation of sound strength varies continuously in musical sound, and that there is interaction between the dynamic changes and the hall acoustics, the term dynamic range [27] is also included in the outer tier.…”
Section: Overviewmentioning
confidence: 99%